Aspectos canônicos da narrativa transmidiática em Lost - Toledo, Glauco Madeira de (Universidade Federal de São Carlos, 2012)
The concept of transmedia storytelling by Henry Jenkins is taken in order to differentiate it from the concept of cross-media, older and worked earlier by several authors. Based on a comparison, it is proposed that the criterion of differentiation is the fact that transmedia storytelling necessarily tells a story and requires a specific type of cohesion of diegetic facts, here called fictional canon. These references are used to analyze an illustrative example: the series LOST (Lost, USA, 2004-2010), created by JJ Abrams, Jeffrey Lieber and Damon Lindelof, and its narrative extensions, since the body of work brings together some pieces that exhibit characteristics of both cross-media and transmedia storytelling, allowing discussion of the criterion of fictional canon. The text discusses the importance of adding the definition of transmedia storytelling the fictional canon variable, to better define the concept and to support future transmedia productions.
Keywords: Comunicação; Narrativa transmidiática; Crossmedia; Canonicidade ficcional; Jenkins III, Henry, 1958-; Lost (Programa de televisão); Transmedia Storytelling; Fictional Canon; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO